MB PROGRAM BIMBINGAN MITIGASI BENCANA BANJIR PADA ANAK USIA SEKOLAH DASAR - fitri aulia; Marfu’atun .; Muhammad Deni Siregar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2018)
The purpose of the present research were disaster mitigation guidance to children who are victims of floods in Selebung, Keruak, East Lombok, NTB. As a form of active contribution of the Guidance and Counseling Study Program in responding to floods that have been experienced by the Selebung community in December 2017. The problems found were anxiety and trauma after flood natural disasters. The solution offered is to carry out post earthquake flood guidance and counseling activities and flood disaster mitigation guidance. The method used: (a) needs analysis, with 3 activities, namely: 1) participant observation, 2) direct interview, 3) games. (b) confirm the target of the activity and establish a good cooperative relationship. (c) implementation of activities (d) monitoring and evaluation. First, implementation have been carried out, it can be concluded as follows: 4, assessment activities. Second, information services about flooding through video screening are coupled with discussion and giving feedback. Third, Painting Therapy. Fourth, Play Therapy. Of the six assessment criteria regarding developments that have been carried out through observation assessment, the average of these activities runs optimally. With an average score of 95.0% - 100%. Only around 2.5% - 5.0% of participants did not provide the maximum response during therapy.